الإعجاز التشريعي في آية الدَّين The Inimitability in Qur'anic Legislation: A Case Study of Verse on Debt - الصوافي (Said Bin Rashid Al Sawafi), سعيد راشد (At-Tajdid - Intellectual Refereed Journal, 2007)
مستخلص البحث الإعجاز القرآني لا حدود له؛ فالقرآن الكريم يخاطب الإنسانية في مختلف العصور والأزمان، فإذا برع العربي في زمن نزول القرآن الكريم في البيان، فإن العصور المتأخرة برعت في أشياء أخرى؛ كالتشريعات مثلاً، وستستمر الحال في تطور وتفاعل متجددين، وقد تظهر مجالات أخرى لم تكن في زماننا، وهذا البحث يُظهر جانبًا من جوانب الإعجاز القرآني؛ هو الإعجاز التشريعي، وقد تناول آية واحدة من كتاب الله هي آية الدَّين؛ لما تحويه من تشريع له أهميته في حياتنا المعاصرة؛ لأنه يتعلق بالمعاملات المالية، وقد تضمن البحث: مقدمة وأربعة مطالب؛ فالمقدمة حوت نبذة عن الموضوع وأهميته، وأهداف البحث، والمنهجية، والخطة، أما المطلب الأول فكان عن مفهوم الإعجاز التشريعي، وقد تناول المعنى اللغوي والاصطلاحي لكلمتي (الإعجاز، التشريع)، والمطلب الثاني آية الدَّين وسمات الإعجاز فيها، والمطلب الثالث فيه بيان وجوه القراءات القرآنية في الآية، أما المطلب الرابع ففيه بيان مفصَّل لما تضمنته آية الدَّين من تشريعات، وأخيرًا الخاتمة حملت أهم النتائج التي توصل إليها البحث. الكلمات الأساسية: الإعجاز، التشريعي، القرآن الكريم، الإعجاز التشريعي، آية الدين. Abstract The holy Quran contains limitless inimitabilities and it meets effectively the needs of all times and ages. As the Arabs excelled in the skill of articulation and literature in the time of revelation, the later generations shined in various fields such as legislation, etc. accordingly in their eras. Undoubtedly, this particular tendency will continue with further inroads, and new areas might come into limelight in the future. The current research aims at exploring one aspect of the Quranic inimitabilities, which is related to the legislation, focusing on āyat al-dayn (the verse on debt) provided it not only carries the implications of legislation but also delivers relevant messages to the financial transactions of contemporary age. This research contains an introduction and four chapters. In the Introduction, the researcher sheds light on lead-in of subject, significance of the study, objectives of research, methodology and plan. The first chapter highlights the concept of legislative inimitabilities including the linguistic and technical definitions of terms ‘inimitability’ and ‘legislation’. The second chapter focuses on the āyat al-dayn and inimitable characteristics imbued within it. The third chapter elucidates the diverse ways of recitation of āyat al-dayn. In the fourth chapter, the researcher offers a thorough examination on the legislative dimensions of āyat al-dayn followed by a conclusion that consists of the significant findings. Keywords: Inimitability, legislation, the holy Quran, inimitability in legislation and āyat al-dayn. Abstrak Kemukjizatan Al-Quran tiada batasannya. Ini kerana Al-Quran berinteraksi dengan manusia pada setiap masa dan zaman. Jika orang Arab pada zaman penurunan Al-Quran terkenal dengan kefasihan bahasa mereka, manusia pada zaman kini pula hebat dalam bidang-bidang lain seperti pensyariatan. Keadaan ini akan sentiasa berkembang dan berterusan. Mungkin suatu hari nanti akan muncul bidang-bidang baru yang belum ada pada zaman kita. Kajian ini mengupas salah satu aspek kemukjizatan Al-Quran iaitu kemukjizatan dari sudut pensyariatan. Kajian membincangkan sepotong ayat sahaja dari Al-Quran, iaitu ayat tentang hutang memandangkan ia mengandungi suatu pensyariatan yang penting dalam hidup masa kini. Hal ini kerana ayat ini berkait rapat dengan muamalat yang melibatkan harta. Kajian ini mengandungi pendahuluan dan empat topik pecahan. Pendahuluan membincangkan tentang maklumat awal mengenai topik kajian iaitu kepentingan topik, objektif, metodologi dan kertas cadangan. Topik pertama membincangkan tentang definisi kemukjizatan pensyariatan dari sudut bahasa dan istilah bagi dua perkataan (I’jaz dan Tasyri’ie). Tajuk kedua pula membincangkan tentang ayat hutang serta kemukjizatannya dari sudut pensyariatan. Topik ketiga pula mengupas tentang pelbagai cara bacaan ayat tersebut menurut qiraat yang berbeza. Topik keempat menjelaskan aspek pensyariatan yang terkandung dalam ayat. Kajian diakhiri dengan dapatan-dapatan penting yang ditemui oleh pengkaji. Keywords: Kemukjizatan, hukum, al- Quran, kemukjizatan dalam hukum, āyat al-dayn..